2019
DOI: 10.1007/s11077-019-09355-1
|View full text |Cite
|
Sign up to set email alerts
|

Cross-boundary policy entrepreneurship for climate-smart agriculture in Kenya

Abstract: Many initiatives to address contemporary complex challenges require the crossing of sector, domain, and level boundaries, which policy entrepreneurs are believed to facilitate. This study aims to enhance our understanding of how, why, and with what effect such entrepreneurs operate to cross boundaries. As this requires an account of both entrepreneurial strategy and the surrounding policy environment, we embed entrepreneurship in the policy frameworks of multiple streams, advocacy coalitions, and punctuated eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…Generally, there is a paucity of literature on CSA mainstreaming in local development plans as most researchers have focused on national discourses ( e.g., Clapp et al 2018 ; Faling and Biesbroek 2019 ; Totin et al, 2018 ; Zougmoré et al 2016 ; Zougmoré et al 2019 ) and CSA adoption by farmers and their implications for agriculture productivity ( e.g., Khonje et al 2018 ; Ng’ombe et al 2017 ; Tankha et al 2020 ). These studies are important for understanding the factors that can inhibit or enhance farmers’ adoption of CSA.…”
Section: The Challenge Of Climate-smart Agriculture Mainstreamingmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, there is a paucity of literature on CSA mainstreaming in local development plans as most researchers have focused on national discourses ( e.g., Clapp et al 2018 ; Faling and Biesbroek 2019 ; Totin et al, 2018 ; Zougmoré et al 2016 ; Zougmoré et al 2019 ) and CSA adoption by farmers and their implications for agriculture productivity ( e.g., Khonje et al 2018 ; Ng’ombe et al 2017 ; Tankha et al 2020 ). These studies are important for understanding the factors that can inhibit or enhance farmers’ adoption of CSA.…”
Section: The Challenge Of Climate-smart Agriculture Mainstreamingmentioning
confidence: 99%
“…Climate-smart agriculture targets adaptive and resilience practices that address climate change impacts on agriculture production (FAO 2017 , p. 1; Tankha et al 2020 , 109), minimizing the sector’s contribution to GHG emissions (Faling and Biesbroek 2019 ; Steenwerth et al 2014 , p. 533) while increasing farmers’ income (Akrofi-Atitianti et al 2018 , p. 10; FAO 2017 , p. 1). CSA forms part of the global call to mainstream climate change in agriculture production (Chandra et al 2018 , p. 526; Newell et al 2018 , p. 54; Tankha et al 2020 , pp.…”
Section: An Overview Of Climate-smart Agriculture Mainstreamingmentioning
confidence: 99%
See 1 more Smart Citation
“…Another reason why climate objectives may be prevalent in policy frames but remain absent from sectoral plans and strategies is international aid. For example, ministries that lead the design of climate policies may try to strategically align themselves with donors to be responsive to their priorities (Faling & Biesbroek, 2019;Walsh, 2017). Analyzing policies on climate-smart agriculture in Kenya, Faling and Biesbroek (2019) found that those advocating for climate-smart agriculture policies pointed to the availability of international climate finance.…”
Section: Climate Mainstreaming As Policy Integrationmentioning
confidence: 99%
“…For example, Skogstad and Wilder (2019) claim that 'multidimensional ideas' not only help create a 'bandwagoning' effect, but also ensure that opposition remains fragmented. Similarly, Faling and Biesbroek (2019) emphasise the importance of employing multiple frames in building cross-sectoral coalitions.…”
Section: Complex Problems Crises and Ideasmentioning
confidence: 99%